Effect of Cr Content on Corrosion Resistance of Fe-Cr-Ni Alloys Exposed in Supercritical Water (SCW) - Mahboubi, Shooka (My University, 2014)
The aim of this work was to rationalize the corrosion resistance of candidate austenitic iron-chromium-nickel (Fe-Cr-Ni) alloys in supercritical water (SCW) for use as fuel claddings within the in-core structure of the Canadian supercritical water-cooled reactor (SCWR) concept. High chromium (Cr)-containing alloys (Alloy 800HT with 20.6 wt.% Cr and 30.7 wt.% Ni and Alloy 33 with 33.4 wt.% Cr and 31.9 wt.% Ni) in the mill annealed condition were chosen for this purpose. Coupons were exposed on a short-term basis (500 h) in a static autoclave containing 25 MPa SCW at 550 °C and 625 °C. Gravimetric measurements and electron microscopy techniques were then used to study the oxidation/corrosion resistance of two alloys. Alloy 33 was found to exhibit the higher corrosion resistance at both temperatures. The improved corrosion resistance of Alloy 33 was attributed to two factors: (i) the formation of a continuous Cr-rich corundum-type M2O3 (M= Cr and Fe) oxide layer that prevented the diffusion of Fe and the formation of a less-protective Fe/Mn-Cr spinel ([Fe,Mn]Cr2O4) outer layer, (ii) a sufficient residual bulk Cr in the Cr-depleted layer adjacent to the alloy/scale interface that prevented any localized internal oxidation from occurring. A mass balance conducted on the corroded Alloy 33 material suggested that volatilization of the corundum-type oxide layer did not occur, at least not within the short-term exposure in the essentially deaerated SCW. A key issue requiring further study was the observation of intermetallic precipitates that formed below the Cr-depleted zone adjacent to the alloy/scale interface in both alloys when exposed for 500 h at 625 °C and their possible influence on the in-service mechanical integrity.
Keywords: Corrosion resistance, Supercritical water-cooled reactor (SCWR), supercritical water (SCW), Cr content, oxide scale